2010
DOI: 10.1186/1471-2458-10-479
|View full text |Cite
|
Sign up to set email alerts
|

The CONSTANCES cohort: an open epidemiological laboratory

Abstract: BackgroundProspective cohorts represent an essential design for epidemiological studies and allow for the study of the combined effects of lifestyle, environment, genetic predisposition, and other risk factors on a large variety of disease endpoints. The CONSTANCES cohort is intended to provide public health information and to serve as an "open epidemiologic laboratory" accessible to the epidemiologic research community. Although designed as a "general-purpose" cohort with very broad coverage, it will particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 30 publications
0
39
0
2
Order By: Relevance
“…Most research has concentrated on specific measures such as coronary heart disease risk, although measures of positive health more generally have been proposed, such as the concept of allostatic load (McEwen & Seeman, 1999) and its current development (Kelly--Irving et al, 2014). New initiatives in the area of positive health would be timely because of the wealth of biomedical data becoming available in large, representative social surveys, such as the Constances cohort (Zins et al, 2010) and the UK Household Longitudinal Study (Benzeval, Devillas, Kumari & Lynn, 2014).…”
Section: Onset Of Chronic Illness and Labour Market Exitmentioning
confidence: 99%
“…Most research has concentrated on specific measures such as coronary heart disease risk, although measures of positive health more generally have been proposed, such as the concept of allostatic load (McEwen & Seeman, 1999) and its current development (Kelly--Irving et al, 2014). New initiatives in the area of positive health would be timely because of the wealth of biomedical data becoming available in large, representative social surveys, such as the Constances cohort (Zins et al, 2010) and the UK Household Longitudinal Study (Benzeval, Devillas, Kumari & Lynn, 2014).…”
Section: Onset Of Chronic Illness and Labour Market Exitmentioning
confidence: 99%
“…Modern biobanking methods allow for the long term conservation of biological material in suitable conditions for later analyses, years to decades after biospecimen collection (Palmer 2007, Zins et al 2010. The SOPs produced will ensure that the quality of the collected and stored material will facilitate future research, including analyses of potential new biomarkers as they are identified through experimental and molecular epidemiological research.…”
Section: Proposed Biomarkersmentioning
confidence: 99%
“…Regular medical check-ups conducted routinely as part of occupational medical surveillance over the workers' careers constitute an unique potential framework for the prospective and repeated collection of biological samples (Laurier et al 2012). A state-of-the-art-biobank centralizing such samples from a fixed cohort of individuals over many years would be a valuable resource for a detailed assessment of the long-term effects of protracted exposure to uranium, as is the case for other types of occupational or environmental exposures (Palmer 2007, Zins et al 2010.…”
Section: Cohorts and Cohort Subsets For Dose Response Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern epidemiological research is often based on a large data sets such as the National Epidemiologic Survey for Alcohol and Related Conditions (NESARC) [9,10,11], the National Health and Nutritional Examination Survey (NHANES) [12]; the CONSTANCES cohort [13], and the Whitehall cohort study [14,15], etc. Problems that scientists face when dealing with such data sets include: multicolinearity (when variables are correlated to each other), confounding factors (when a risk factor is correlated with both exposure and outcome variable), interactions (when the direction or magnitude of an association between two variables differs due to the effect of a third variable), the sample size (the study can be too large with meaningful associations being declared or too small to detect important associations), and the number of factors being studied (the higher the number of factors the higher is the probability to find interactions due to chance alone) [16].…”
Section: Current Practices For Variable Selection In Epidemiological mentioning
confidence: 99%